42x-12=-10-7x

Simple and best practice solution for 42x-12=-10-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42x-12=-10-7x equation:


Simplifying
42x + -12 = -10 + -7x

Reorder the terms:
-12 + 42x = -10 + -7x

Solving
-12 + 42x = -10 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-12 + 42x + 7x = -10 + -7x + 7x

Combine like terms: 42x + 7x = 49x
-12 + 49x = -10 + -7x + 7x

Combine like terms: -7x + 7x = 0
-12 + 49x = -10 + 0
-12 + 49x = -10

Add '12' to each side of the equation.
-12 + 12 + 49x = -10 + 12

Combine like terms: -12 + 12 = 0
0 + 49x = -10 + 12
49x = -10 + 12

Combine like terms: -10 + 12 = 2
49x = 2

Divide each side by '49'.
x = 0.04081632653

Simplifying
x = 0.04081632653

See similar equations:

| 7x-4=-171 | | 6b^2-13b+13=0 | | -6j+15j=-9 | | 3(x+5x)=104 | | -8b+20b+6=-18 | | 2-[x-(3-2x)]=4 | | x^2+9xy+8y^2= | | 9x-8x+7=-10 | | 2/3(6p+18)= | | 5+7x-3x=6x+9+4 | | 9w+19w-14w+7w+-3w=-18 | | 4-4y+4y=4 | | 2(x-5)+3(x-4)=2x-4 | | 2/5w=20 | | 50/3*40/7 | | 0=-4m^2-11m-6 | | -4x-5=-3x | | 5+5/7 | | z-3+3=11+3 | | 4x-6=-12x+16 | | 0.5m-4=5 | | 16x^2-23x+69=0 | | x=2-2y | | y-.50=.66 | | 16x^2-23x+348=0 | | y/16=24 | | 0.07-0.01(x+1)=0.02(3-x) | | 9x=10x+15 | | 6x-2x-18=6 | | 7c-4=32 | | 2/5h+g=d | | 2(x+4)-5=6x-4(-1+x) |

Equations solver categories